Areas with evidence of equity and their progress on mortality from tuberculosis in an endemic municipality of southeast Brazil - Mellina YAMAMURA; Marcelino SANTOS NETO; Francisco CHIARAVALLOTI NETO; Luiz Henrique ARROYO; Antônio Carlos Vieira RAMOS; Ana Angélica Rêgo de QUEIROZ; Aylana de Souza BELCHIOR; Danielle Talita dos SANTOS; Juliane de Almeida CRISPIM; Ione Carvalho PINTO; Severina Alice da Costa UCHÔA; Regina Célia FIORATI; et al. (BMC, 2017)
Abstract Background In Brazil, people still fall ill and die from tuberculosis (TB), and this can be explained by the significant impasse in the equity of distribution of therapeutic resources to the population as a whole. The aim was to identify geographical areas which have shown progress in terms of equity (of income, schooling and urban occupancy) and test its effect on mortality from TB in a municipality of southeast Brazil. Methods It is an ecological study considering TB as the basic cause for deaths registered between 2006 and 2013 on the Mortality Information System and other variables obtained through the Demographic Census of the Brazilian Institute of Geography and Statistics (2010). The geographical area for analysis comprised the areas of coverage of the health services. Social indicators have been constructed through the Principal Component Analysis (PCA). The cases were geocoded and the annual mortality rate from TB was calculated with smoothing using the local empirical Bayesian method. Multiple linear regression was then performed. There was confirmation of the existence of spatial dependence of residue through the application of the Global Moran I test, and application of the Models with Global Spatial Effects, to identify the best standard of spatial regression. Results The mortality rates ranged from 0.00 to 2.8 deaths per 100,000 people, per year. In the PCA, three indicators were constructed, and designated as indicators of income, social inequality, and social equity. In multiple linear regression, the indicator of social equity was statistically significant (P < 0.0001) but had a negative association, an adjusted R2 of 28.36% and with spatial dependence (Moran I = 0.21, P = 0.003455). The best model to deal with existing spatial dependence was the Spatial Lag Model. Conclusions The better social conditions have shown progress in reducing mortality from TB, thereby reinforcing the achievement of Sustainable Development Goals. In addition, cartography was also applied, which can be replicated in other scenarios throughout the world, using a scope distinct from that of works traditionally produced in that it places the emphasis on social equity.